2009
DOI: 10.1007/s10661-008-0745-0
|View full text |Cite
|
Sign up to set email alerts
|

Ionic species associated with PM2.5 in the City of Guadalajara, México during 2007

Abstract: Atmospheric aerosol particles were collected from January to December 2007 at two sites in the City of Guadalajara. The first site (Centro) is located in the downtown, which is characterized by high vehicular traffic, and the second site (Miravalle) is in the southern part of the city, characterized by emissions from high industrial and vehicular activity. Sulfates, nitrates, and ammonium were the most abundant ions at both sites. Similar concentrations of sulfates, nitrates, and ammonium were observed through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
2
3
0
1
Order By: Relevance
“…Thus, those atmospheric particles had acidic properties during this sampling period. These results are consistent with those previously reported [28] for the Centro site in 2007, taking into account the same ionic species, while in Miravalle a slope of about 1.0 (1.08) was obtained, indicating neutralization processes, which is different than that observed during a previous study [28]. Thus, there were enough cations to neutralize the sulfate and nitrate present in the Miravalle environment, which likely originated either by contribution of additional cations from resuspended particles (Ca 2+ , Mg 2+ ) or from being buffered by the higher average concentrations of NH 4 + found in Miravalle [58], which were almost two-fold of that measured in Centro (Table 4).…”
Section: Potential Sources Of Ionic Species In Pm 25supporting
confidence: 94%
See 3 more Smart Citations
“…Thus, those atmospheric particles had acidic properties during this sampling period. These results are consistent with those previously reported [28] for the Centro site in 2007, taking into account the same ionic species, while in Miravalle a slope of about 1.0 (1.08) was obtained, indicating neutralization processes, which is different than that observed during a previous study [28]. Thus, there were enough cations to neutralize the sulfate and nitrate present in the Miravalle environment, which likely originated either by contribution of additional cations from resuspended particles (Ca 2+ , Mg 2+ ) or from being buffered by the higher average concentrations of NH 4 + found in Miravalle [58], which were almost two-fold of that measured in Centro (Table 4).…”
Section: Potential Sources Of Ionic Species In Pm 25supporting
confidence: 94%
“…The environmental levels of inorganic species are of the same order of magnitude as those already reported in an earlier study [28]. The statistical analysis, via the Mann-Whitney U test, showed that the higher median concentration of NO 3´w as in Miravalle.…”
Section: Potential Sources Of Ionic Species In Pm 25supporting
confidence: 80%
See 2 more Smart Citations
“…Tales son los casos de zonas metropolitanas como el Valle de México, Guadalajara y Monterrey. [11][12][13][14] Sin embargo, en la mayoría de las zonas provinciales de la República Mexicana, existe poca información al respecto, tal es el caso de la Ciudad de San Francisco de Campeche, capital del Estado de Campeche, la cual presenta un clima tropical húmedo 15 convirtiéndola en una locación idónea para la realización de estudios de evaluación temprana de calidad del aire. Así mismo, la ciudad es considera Patrimonio Cultural de la Humanidad por la UNESCO desde 1999, por lo que se pretende realizar un estudio sobre contaminantes atmosféricos y su relación con variables meteorológicas en la ciudad y evaluar los efectos de los aerosoles atmosféricos sobre la población y materiales de interés histórico-artístico.…”
Section: Introductionunclassified